Downregulation of Long Non-coding RNA Nuclear Paraspeckle Assembly Transcript 1 Inhibits MEG-01 Differentiation and Platelet-Like Particles Activity - Weihua Bian; Wangping Chen; Xiaoli Jiang; Huiqing Qu; Jing Jiang; Jinfu Yang; Xinyue Liang; Bingrui Zhao; Yeying Sun; Chunxiang Zhang (Frontiers in Genetics, 2020)
Platelets are derived from megakaryocytes and play an important role in blood coagulation. By using high throughput sequencing, we have found that the long non-coding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 (NEAT1) is abundant in platelets (GEO ID: 200097348). However, little is known about its role in regulating megakaryocyte differentiation and platelet activity. This study aims to clarify the effect of NEAT1 on MEG-01 differentiation and platelet-like particle (PLP) activity. NEAT1 in MEG-01 cells was knocked down by siRNA transfection. The adhesion of MEG-01 and PLP to collagen-coated coverslips was observed under a fluorescence microscope. Flow cytometry was used to investigate cell apoptosis, cell cycle, the levels of D41/CD42b on MEG-01 cells and CD62P on PLPs. Quantitative real-time polymerase chain reaction was used to detect NEAT1 and IL-8 expression levels. Western blot was used to measure the protein levels of Bcl-2, Bax, cleaved caspase-3, and IL-8. RNA-binding protein immunoprecipitation was used to detect the interaction of NEAT1 and splicing factor proline/glutamine-rich (SFPQ). Results showed that NEAT1 knockdown decreased the adhesion ability of thrombin-stimulated MEG-01 and PLP. The expression of CD62P on PLPs and CD41/CD42b on MEG-01 cells was inhibited by NEAT1 knockdown. In addition, NEAT1 knockdown inhibited cell apoptosis with increased Bcl2/Bax ratio and decreased cleaved caspase-3, and reduced the percentage of cells in the G0/G1 phase. Meanwhile, NEAT1 knockdown inhibited the expression of IL-8. A strong interaction of NEAT1 and SFPQ, a transcriptional repressor of IL-8, was identified. NEAT1 knockdown reduced the interaction between SFPQ and NEAT1.The results suggest that lncRNA NEAT1 knockdown decreases MEG-01 differentiation, PLP activity, and IL-8 level. The results also indicate that the regulation of NEAT1 on IL-8 may be realized via a direct interaction between NEAT1 and SFPQ.